(untitled) (Canadian Dermatology Today, 2023)
Patients with cutaneous findings of systemic autoimmune rheumatological disease often require a multidisciplinary approach to diagnosis and management. In general, the first signs of systemic rheumatological diseases may be skin manifestations, which prompt those affected to visit the dermatology clinic. The basis and presentations of conditions such as systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are complex, and involve genetic and environmental influences that are embedded in broad and overlapping factors of the socioecological model. This review recognizes that North American Indigenous (NAI) peoples are diverse, by region, language, culture, home environment, and more; therefore, generalizations are not intended. Furthermore, interpretations of the literature are limited by factors such as region and location (e.g., remote-rural vs. urban), sample size, study design, and statistical interpretations. Additionally, knowledge of biological and genetic predispositions of autoimmune diseases in the NAI population is lacking and beyond the scope of this article. The use of racial and ethnic terminologies can vary greatly and is often based in social concepts. These terms are also used in the context of current categorizations employed by the US Census or as categories that are often used in clinical trials. Thus, further use of the term “North American Indigenous” (NAI) in this article takes this into account. It is worth noting that commonalities surrounding historical contexts and barriers to care are found for many NAI individuals and communities, for example for those living rurally and remotely. The purpose of this review is to provide a broad overview of what is known about mostly regional prevalence data and disease characteristics of autoimmune diseases such as SLE and SSc in the NAI population. Unique considerations surrounding barriers to care reported to be faced by some NAI populations will also be explored.